The Industry's Perspectives on the Learners' Needs to Prepare the English Course Materials - Pikir Wisnu Wijayanto (Universitas Muhammadiyah Semarang, 2017)
This study aims at identifying the industrys perspectives on the learners needs in order to prepare the English course materials for the Computer Engineering students. The identification done by investigating the assistant managers/managers from IT industry perspective which focused on the learners needs in term of the English course materials. This research adopted a mixed methods of explanatory design to investigate the learners needs.The sample of the study consisted of 10 assistant managers/managers from Telkom Akses Company. Then, the data were collected and generated from their perspectives answers on the questionnaires and semi-structured interviews. The results showed that the main purpose of learners to learn English was for social purposes, and the content areas should focus on IT field workers. Then, the English language to be used should only dealt with speaking and vocabulary that emphasized on the presentation in a meeting in order to develop their professional communication.